1958
DOI: 10.1126/science.128.3336.1431
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Relation between Metals and Natural Pigments

Abstract: search Laboratories were used. Infrared spectra were obtained on a Perkin-Elmer model 21, double-beam instrument; a barium fluoride cell (0.052 mm) and a transmittance screen in the reference beam (3) were used. The spectrum of water has been published (3), and our spectrum for water corresponds to it.A 20 percent (weight by volume) solution of CDMT was prepared and scanned as soon as possible after dilution to the mark, scanned again 5 minutes after dilution, and then scanned every 30 minutes thereafter for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1960
1960
1993
1993

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…On the brown leghorn, Goodale (1913), Domm( 1927) and Juhn andGustanson (1930, 1932) found that the structure and the color of feathers were due to the presence of estrogens.Namely,it was found that female feathers changes by ovariectomy to the male-like and that male given estrogen becomes the female type. Kikkawa and Ogita (1955a, b )and Kikkawa et al(1958) suggested that there is a certain relationship between metals and colors of the fur of guinea pigs. Albert (1950a, b, c and d) confirmed that active substances such as riboflavin, folic acid, amino acids and peptides could chelate with copper in vivo.…”
Section: Japan Racing Associationracehorse Healthmentioning
confidence: 99%
“…On the brown leghorn, Goodale (1913), Domm( 1927) and Juhn andGustanson (1930, 1932) found that the structure and the color of feathers were due to the presence of estrogens.Namely,it was found that female feathers changes by ovariectomy to the male-like and that male given estrogen becomes the female type. Kikkawa and Ogita (1955a, b )and Kikkawa et al(1958) suggested that there is a certain relationship between metals and colors of the fur of guinea pigs. Albert (1950a, b, c and d) confirmed that active substances such as riboflavin, folic acid, amino acids and peptides could chelate with copper in vivo.…”
Section: Japan Racing Associationracehorse Healthmentioning
confidence: 99%